The Effect of Job Satisfaction as Mediation between Motivation and Compensation on the Performance of Extraordinary School Teachers in Batam City - Go, Michelle; Dini, Yuli Indah Fajar; Mon, Muhammad Donal (Jurnal Manajemen (Edisi Elektronik), 2024)
This research aims to identify and evaluate how the relationships between variables that are contained in this research determine the performance of SLB teachers in Batam City. The SLB teachers were selected as the subject of this research because they hold a great and crucial responsibility in educating and fostering children with special needs. Quantitative approach and purposive sampling were conducted, collecting 84 respondents from 7 out of 8 SLB in Batam City, either who have the status of honorary, contract, or permanent teachers. SmartPLS version 3.2.9 was also used as an analytical tool in this research. The results that have been obtained show that job satisfaction is proven to play an important role as a mediating variable whilst also being significantly influenced by motivation and compensation. Aside from that, employee performance can be significantly influenced by motivation and job satisfaction, but not by compensation. Therefore, it is necessary to maintain the high level of motivation of the SLB teachers, because an increase in motivation simultaneously maintains the level of job satisfaction and boosts the productivity of their performance in carrying out all of their responsibilities.